Public Management Model in Marine Pollution Control; A Case Study of Bintan Regency - Fitri Kurnianingsih; Syafrianita Syafrianita; Armauliza Septiawan (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
Marine pollution is one of the most pressing environmental challenges in coastal areas, particularly in areas with intensive shipping and tourism activities such as Bintan Regency, Indonesia. Recurrent oil spills, accumulation of marine debris and microplastics, and degradation of mangrove and coral reef ecosystems highlight the need for an integrated governance model capable of ensuring both ecological sustainability and the socio-economic resilience of coastal communities. This study aims to assess the performance of public management in controlling marine pollution in Bintan and propose a governance model that emphasizes strengthening institutional coordination, preventive measures, and accountability mechanisms. The method used is a case study with a qualitative-descriptive approach, based on secondary data obtained from government documents, environmental regulations, media reports, and international scientific articles. Data were analyzed using thematic content analysis techniques to identify key issues, institutional roles, and the effectiveness of policy instruments. The results show that although regulatory frameworks such as PP No. 19/1999, DIKPLHD Bintan, and MARPOL obligations are in place, implementation in the field remains fragmentary and reactive, reflected in the recurrence of black oil pollution and limited ship waste reception facilities. This study emphasizes the importance of a polycentric governance model that integrates Integrated Coastal Zone Management (ICZM), collaborative governance between state and non-state actors, and economic instruments such as indirect fee schemes for wastewater treatment facilities. In conclusion, strengthening monitoring capacity, participatory evaluation, and multi-level actor integration are key to reducing the rate of recurrent pollution while protecting Bintan's coastal ecosystems and communities.